KETERLIBATAN ORGANISASI GERAKAN MAHASISWA NASIONAL INDONESIA (GMNI) CABANG SURAKARTA PADA PERISTIWA REFORMASI 1998 DI KOTA SOLO - Nugroho, Deni Agung; Muslikh, Muslikh; Andriyanto, Andriyanto (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2022)
This research examines the organization of GMNI Surakarta Branch. GMNI Surakarta Branch itself had a role in the 1998 reform event in Solo City, namely participating in making concepts in demonstrations in Solo City, GMNI Surakarta Branch itself also actively included its cadres in internal campus organizations and alliances on several campuses as an example SMPR, SMPTA and DRMS. This study uses the Historical Method. GMNI is one of the largest organizations in Indonesia through one of its branches, namely the Surakarta branch which was also involved in the 1998 reform event. GMNI Surakarta Branch itself is also active in including its cadres in internal campus organizations and alliances on several campuses for example SMPR, SMPTA and DRMS. Another role and involvement is that GMNI Surakarta Branch also took an active part in issuing statements as a critique of several New Order policies which were not in favor of the Indonesian people in several print media institutionally, GMNI Surakarta Branch also played a role in forming the FKPI (Indonesian Youth Nationality Forum) which included there are several external campus organizations minus HMI and several other youth organizations. The impact of the reform itself in the city of Solo on governance is also not much different from conditions nationally, starting from the leadership, namely the Mayor and members of the central and regional legislatures who are held by active members of the military after the reform the members of the military began to no longer serve in these political positions. In terms of economy, the city of Solo is a city that quickly recovered from the 1998 riots among other cities in Central Java.